Reply to Frański, R.; Beszterda-Buszczak, M. Comment on "Villalva et al. Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori. Antioxidants 2022, 11, 1849" - Marisol Villalva; Jose Manuel Silvan; Teresa Alarcón-Cavero; David Villanueva-Bermejo; Laura Jaime; Susana Santoyo; Adolfo J. Martinez-Rodriguez (MDPI AG, 2023)
Franski and Beszterda-Buszczak [...]